How can the dental surgeon promote oral health in patients submitted to chemotherapy? - de Souza Lessa, Mariana; Patussi, Cleverson; Ferrairo Danieletto Zanna, Carolina; Moacir Sassi, Moacir Sassi; Zanna Ferreira , Gustavo (Brazilian Dental Science, 2022)
Lesions that affect the oral cavity resulting from chemotherapy can lead to systemic impairment, increasing the length of hospital stay, impairing the patient’s quality of life. Through a integrative review, this work aims to show the conduct and importance of dentists in promoting oral health and preventing an oral infectious focus. The search was performed in the Pubmed, Cochrone, SciElo and Virtual Health Library (VHL) databases, using the descriptors in English, oral care and Chemotherapy and Cancer treatment and dentistry, filtering only articles in English and published between 2006 and 2021. The search located six hundred and twenty articles, but only seven met the search criteria. One author used a mouthwash containing propolis where 65% of patients were cured on the seventh day after the onset of oral mucositis (OM) lesions. One author used cryotherapy with chamomile infusion, patients who underwent this approach did not pass grade I, being effective in reducing the occurrence of OM, and the other two authors proposed a protocol for oral cavity care. All authors obtained satisfactory results. KEYWORDS Dentistry; Antineoplastics; Oncology.